Sensor cascading fault estimation and control for hypersonic flight vehicles based on a multidimensional generalized observer - Chen, Fuyang (2021)
This study presents a sensor cascading fault estimation and fault-tolerant control (FTC) for a nonlinear Takagi-Sugeno fuzzy model of hypersonic flight vehicles. Sensor cascading faults indicate the occurrence of source fault will cause another fault and the interval between them is really short, which makes it difficult to handle them in succession. A novel multidimensional generalized observer is used to estimate faults by integrating constant offset and time-varying gain faults. Then, a fault-tolerant controller is used to solve system nonlinearity and sensor fault problems. The observer and controller satisfy the performance index and are robust to external disturbances. A sufficient condition for the existence of observer and controller is derived on the basis of Lyapunov theory. Simulation results indicate the effectiveness of the proposed fault estimation and FTC scheme.